Genetic variation in the vitamin D related pathway and breast cancer risk in women of African ancestry in the root consortium. Issue 1 (23rd September 2017) - Wang, Shengfeng; Huo, Dezheng; Kupfer, Sonia; Alleyne, Dereck; Ogundiran, Temidayo O.; Ojengbede, Oladosu; Zheng, Wei; Nathanson, Katherine L.; Nemesure, Barbara; Ambs, Stefan; Olopade, Olufunmilayo I.; Zheng, Yonglan
Abstract : The vitamin D related pathway has been evaluated in carcinogenesis but its genetic contribution remains poorly understood. We examined single‐nucleotide polymorphisms (SNPs) in the vitamin D related pathway genes using data from a genome‐wide association study (GWAS) of breast cancer in the African Diaspora that included 3, 686 participants (1, 657 cases). Pathway‐ and gene‐level analyses were conducted using the adaptive rank truncated product test. Odds ratios (OR) and 95% confidence intervals (CI) were estimated at SNP‐level. After stringent Bonferroni corrections, we observed no significant association between variants in the vitamin D pathway and breast cancer risk at the pathway‐, gene‐, or SNP‐level. In addition, no association was found for either the reported signals from GWASs of vitamin D related traits, or the SNPs within vitamin D receptor (VDR) binding regions. Furthermore, a decrease in genetically predicted 25(OH)D levels by Mendelian randomization was not associated with breast cancer ( p  = 0.23). However, an association for breast cancer with the pigment synthesis/metabolism pathway almost approached significance (pathway‐level p  = 0.08), driven primarily by a nonsense SNP rs41302073 in TYRP1, with an OR of 1.54 (95% CI = 1.24–1.91, p adj  = 0.007). In conclusion, we found no evidence to support an association between vitamin D status and breast cancer risk in women of African ancestry, suggesting that vitamin D is unlikely to have significant effect on breast carcinogenesis. Interestingly, TYRP1 might be related to breast cancer through a non‐vitamin D relevant mechanism but further studies are needed. Abstract : What's new? Emerging evidence links vitamin D with protection from breast cancer. Here the authors explored the role of genetic variants in vitamin D‐related genes in breast carcinogenesis among women of African descent, a group afflicted with high breast cancer risk and vitamin D deficiency due to dark skin pigmentation. Combining bioinformatics and experimental evidence, they found no evidence to support the association between vitamin D status and breast cancer risk.